Rowell syndrome - Ramesh Y Bhat; Chaitanya Varma; Sonia Bhatt; C Balachandran (Wolters Kluwer Medknow Publications, 2014)
Rowell syndrome is a rare disease consisting of erythema multiforme-like lesions associated with lupus erythematosus. The syndrome occurs mostly in middle-aged women. The authors describe the syndrome in a 15-year-old boy who responded well to systemic steroids and hydroxychloroquine.